Bad bootstrapping: the problem with third-factor replies to the Darwinian Dilemma for moral realism. - Dyke, Michelle M. (Philosophical Studies, 2020)
Street's (Philos Stud 127:109–166, 2006) "Darwinian Dilemma" is a well-known epistemological objection to moral realism. In this paper, I argue that "third-factor" replies to this argument on behalf of the moral realist, as popularized by Enoch (Philos Stud 148(3):413–438, 2010, Taking morality seriously: a defense of robust realism, Oxford University Press, Oxford, 2011), Skarsaune (Philos Stud 152(2):229–243, 2011) and Wielenberg (Ethics 120(3):441–464, 2010, Robust ethics: the metaphysics and epistemology of godless normative realism, Oxford University Press, Oxford, 2014), cannot succeed. This is because they are instances of the illegitimate form of reasoning known as "bootstrapping." The phenomenon of bootstrapping has been discussed in detail, most notably by Vogel (J Philos 97(11):602–623, 2000) and Cohen (Philos Phenomenol Res 65(2):309–329, 2002), in a different context as an objection to reliabilism and related theories of knowledge. I introduce four different characterizations of the error of bootstrapping from the epistemic literature in order to argue that the form of reasoning exemplified by third-factor replies would be deemed illegitimate by every one of them. I conclude that the moral realist should abandon third-factor replies, or else suggest a novel diagnosis for what goes wrong in bootstrapping cases that does not apply equally to the realist's form of argument. However, I am not optimistic about the prospects for this latter strategy.